Simultaneous Determination and Pharmacokinetic Study of Quercetin, Luteolin, and Apigenin in Rat Plasma after Oral Administration of Matricaria chamomilla L. Extract by HPLC-UV. (8th March 2017) - Dong, Xiaoxv; Lan, Wei; Yin, Xingbin; Yang, Chunjing; Wang, Wenping; Ni, Jian
Abstract : A simple and sensitive HPLC-UV method has been developed for the simultaneous determination of quercetin, luteolin, and apigenin in rat plasma after oral administration of Matricaria chamomilla L. extract. The flow rate was set at 1.0 ml/min and the detection wavelength was kept at 350 nm. The calibration curves were linear in the range of 0.11–11.36 μ g/ml for quercetin, 0.11–11.20 μ g/ml for luteolin, and 0.11–10.60 μ g/ml for apigenin, respectively. The intraday and interday precisions (RSD) were less than 8.32 and 8.81%, respectively. The lower limits of quantification (LLOQ) of the three compounds were 0.11 μ g/ml. The mean recoveries for quercetin, luteolin, and apigenin were 99.11, 95.62, and 95.21%, respectively. Stability studies demonstrated that the three compounds were stable in the preparation and analytical process. The maximum plasma concentration (C m a x ) was 0.29 ± 0.06, 3.04 ± 0.60, and 0.42 ± 0.10 μ g/ml, respectively. The time to reach the maximum plasma concentration (T m a x ) was 0.79 ± 0.25, 0.42 ± 0.09, and 0.51 ± 0.13 h, respectively. The validated method was successfully applied to investigate the pharmacokinetics study of quercetin, luteolin, and apigenin in rat plasma after oral administration of M. chamomilla extract.